KOMUNIKASI DALAM KEPEMIMPINAN PENDIDIKAN (STUDI KASUS DI SD MUHAMMADIYAH KLECO, KOTAGEDE, YOGYAKARTA) - Nilna Milhatan Nasihah; Anaas Tri Ridlo Dina Yuliana (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2018)
Communication is very important position, especially in terms of educational leadership. The purpose of this research is to describe and obtain information about communication approach and its implementation in education leadership in SD Muhammadiyah Kleco, Kotagede, Yogyakarta. This research was conducted by using qualitative descriptive approach because it needed deep and accurate data and can describe clearly and detail. Subjects of this study were principals, teachers, and employees. Data collection was done by observation and interview. The result of the research shows that the approach of communication in the leadership of education in SD Muhammadiyah Kleco, Kotagede, Yogyakarta, the principal implements the approach of structure and function of organization, human relations approach, communication approach as organizing process, and organization approach as culture. From various leadership communication approaches in the education, leaders are able to master their communication skills and utilize existing resources to overcome limitations and compose and deliver messages that provide guidance, direction, and motivation to others to act.Keywords: communication, educational leadership